2021
DOI: 10.1242/dev.199805
|View full text |Cite
|
Sign up to set email alerts
|

CFAP61 is required for sperm flagellum formation and male fertility in human and mouse

Abstract: Defects in the structure or motility of cilia and flagella may lead to severe diseases such as primary ciliary dyskinesia (PCD), a multisystemic disorder with heterogeneous manifestations affecting primarily respiratory and reproductive functions. We report that CFAP61 is a conserved component of the Calmodulin and radial Spoke associated Complex (CSC) of cilia. We find that a CFAP61 splice variant, c.143+5G>A, causes exon skipping/ intron retention in human, inducing a multiple morphological abnormalit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 67 publications
0
26
0
Order By: Relevance
“…About 35–60% of MMAF infertility cases are associated with a genetic etiology, and MMAF has been reported to be associated with a variety of genes in humans and in mice [ 9 ]. In previous studies, several gene-families were identified to be associated with flagella, including the AKAP family, DANI family, DNAH family, RSPH family, CCDC family, CFAP family, TTC family, and some single genes [ 1 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. In the AKAP family, AKAP3 and AKAP4 mutations were identified causing dysplasia of the fibrous sheath, presenting MMAF phenotypes and male infertility [ 12 , 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…About 35–60% of MMAF infertility cases are associated with a genetic etiology, and MMAF has been reported to be associated with a variety of genes in humans and in mice [ 9 ]. In previous studies, several gene-families were identified to be associated with flagella, including the AKAP family, DANI family, DNAH family, RSPH family, CCDC family, CFAP family, TTC family, and some single genes [ 1 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. In the AKAP family, AKAP3 and AKAP4 mutations were identified causing dysplasia of the fibrous sheath, presenting MMAF phenotypes and male infertility [ 12 , 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in CCDC39, CCDC40, and CCDC103 presented cilia axonemal disorganization, absent inner dynein arms, and male infertility [ 27 , 28 , 29 ]. Several CFAP family genes were associated with cilia and flagella abnormalities in human and mutant mouse models, including CFAP43, CFAP44, CFAP58, CFAP61, CFAP65, CFAP69, CFAP70, and CFAP251, are associated with flagellum biogenesis and morphogenesis, when mutant, caused MMAF and male infertility [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. Furthermore, whole-exome sequencing (WES) identified FSIP2, DZIP1, and QRICH2 were associated with MMAF, and defected the axoneme [ 40 , 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, among the reported causative genes, few are directly related to FSs. FSIP2 , which encodes a FS-interacting protein, is involved in FS assembly, and FSIP2 defects have been reported to be related to MMAF ( Martinez et al, 2018 ; Liu Y. et al, 2019 ; Liu S. et al, 2021 ; Fang et al, 2021 ; Hou et al, 2022 ; Yuan et al, 2022 ; Zheng et al, 2022 ). In patients harboring FSIP2 mutations, the defects in sperm are not limited to abnormalities in the FS but also cause abnormalities in the microtubule skeleton.…”
Section: Pathogenic Genes and Their Function Inspermatogenesismentioning
confidence: 99%
“…Interestingly, in humans, mutations in genes orthologous to SPEF2A (SPEF2) and CFAP69 turned out to cause MMAF and very rarely PCD (until now, only mutations in SPEF2 were connected to PCD) [190][191][192][193][194][195]. Among other MMAF-causative genes [196,197] studied in Tetrahymena are, as mentioned before, CFAP43 and CFAP44 [127,[198][199][200][201][202], the CSC subunits CFAP61 [203,204] and CFAP251 [204,205], and CFAP206, which forms a part of the RS2 base [126,196].…”
Section: Ciliate: Tetrahymena and Parameciummentioning
confidence: 99%